(untitled) (Faridpur Medical College Journal, 2021)
COVID-19 is primarily a respiratory disease caused by a newly discovered SARS-CoV-2 virus and identified in the city of Wuhan, China in December 2019. World Health Organization (WHO) has declared this disease as a pandemic, and warned other countries. Presently this has affected 221 countries, areas or territories worldwide, Spreading of this disease is very fast in USA, India, Brazil, and Russia than in the country of its origin China. Like other coronaviruses, this may develop respiratory tract infections in the patients range from mild to fatal illness like pneumonia and acute respiratory distress syndrome (ARDS). Bangladesh, a country of 170 million people, is not an exception regarding COVID-19; it has been reported 5,70,800 confirmed cases with 8690 documented deaths. Still now no effective drug, vaccine, or any procedure is available and experiments are underway. However, empirical therapy is being followed to manage and save the lives of the patients. There is a need for pharmacological alternatives to combat this deadly virus and its complications. Based on the previous experiences with similar coronavirus management and present preliminary data from uncontrolled studies, drugs like Chloroquine, Hydroxychloroquine, Remdesivir, Lopinavir/Ritonavir, and Favipiravir have been recommended by the researchers to manage COVID-19. This review had assessed the potential mechanisms, safety profile, availability and cost of these drugs. This review concludes that the drugs mentioned above are having different properties and act differently in combating the COVID-19 viruses. Faridpur Med. Coll. J. 2021;16(1):45-51